TEACHING ENGLISH IN THE DIGITAL ERA - Hasanah, Nur Izatil (STIT Ibnu Rusyd Tanah Grogot, 2020)
The global use of technology might have influenced all of education institutions to follow the current trend of the technological usage. The use of information and communication technology or ICT become a key role in improving education.The study aimed to determine the digital tools utilized by the teachers and how the English teachers perceived teaching English in the digital era, how English teachers cope with the technological innovations and the way they look at the future of English teaching and learning with advent of digital learning. The study employed the qualitative method with interview as the instruments in gathering data among the 10 English teachers at USANT, Iriga City, Philippines. Results show that the respondents or key informants the most widely used are mobile phone, laptop, tablets, computer, e-mail, and Google Translator, while the least widely used are Grammarly, MOOC and Kahoot!. Google Classroom, Edmodo, digital boards, and Quizlet. Moreover, English teachers cope with technological innovations in three ways: first, is by learning through self- discovery; second, by attending trainings and seminars related to technology and digital learning and third, by seeking help from peers. This research concluded that the English teachers use digital tools for English language teaching as supplemental aids; that technology cannot substitute an English teacher; English teachers cope with the technological innovations gradually be learning by themselves, with others and by attending seminars; the English teachers are responsive to the changes in technology.